1972
DOI: 10.1136/bmj.3.5822.323
|View full text |Cite
|
Sign up to set email alerts
|

Infective Factors in Exacerbations of Bronchitis and Asthma

Abstract: possible case of diabetes for the first time plasma glucose values ought to be reported. If anticoagulants interfere with the precipitating second antibody of double antibody insulin assay systems then separation of insulin ought to be achieved by other methods-for example, by adsorption to charcoal. They are equally efficient and simple to use.Glucose and insulin responses are being studied under widely varying circumstances-relation between mother and fetus, hypoglycaemic disturbances in the neonate, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 10 publications
2
39
1
Order By: Relevance
“…First, other studies in which symptom-free patients or 'controls' were investigated have shown that viruses are more frequently isolated from those who have respiratory symptoms than from those who are symptom-free (M.R.C. Report, 1965;Hurrell, Sturdy, Frood & Gardner, 1971;Lambert & Stern, 1972;Poole & Tobin, 1973;Horn & Yealland, 1974). Secondly, in this survey, as in the two large surveys of the Medical Research Council (M.R.C.…”
Section: Discussionmentioning
confidence: 85%
“…First, other studies in which symptom-free patients or 'controls' were investigated have shown that viruses are more frequently isolated from those who have respiratory symptoms than from those who are symptom-free (M.R.C. Report, 1965;Hurrell, Sturdy, Frood & Gardner, 1971;Lambert & Stern, 1972;Poole & Tobin, 1973;Horn & Yealland, 1974). Secondly, in this survey, as in the two large surveys of the Medical Research Council (M.R.C.…”
Section: Discussionmentioning
confidence: 85%
“…32,33 In addition, exposure to children in family studies of respiratory illness is a known risk factor for viral transmission. 34 Thus, it is not surprising that exposure to school children was associated with risk of HRV infection in our study. However, the association with symptomatic disease is more puzzling.…”
Section: Discussionmentioning
confidence: 87%
“…Lambert and Stern (1972) cultured sputum and nasal and throat swabs from two asthmatic subjects, one of whom was a child, and recovered virus in 5 of 11 exacerbations. In the present study of wheezy bronchitis of childhood a virus was isolated from 49 % of episodes, and the sputum samples collected within 5 days of onset of symptoms gave a virus isolation rate of 41 %.…”
Section: Discussionmentioning
confidence: 99%